An Emotional Experience of Work: Attachment Orientations and Emotion Expressions to Work-Related Film Stimuli - Seitl, Martin; Omastová, Eva; Sulejmanov, Filip; Hess, Ursula; Hareli, Shlomo; Dostál, Daniel; Hypsova, Petra; Kafetsios, Konstantinos (Studia Psychologica, 2023)
The present study investigated individual differences in attachment orientation at work as they relate to workers' facial expressions to work-related emotions. In a laboratory study, sixty employees completed the Experiences in Work Relationships-Individual Scale (EWR-I), which assesses attachment-related regulation strategies at work. Participants' facial expressions while viewing film clips from a work environment series were assessed using a computerized facial analysis software. Results showed that higher avoidant attachment was associated with lower average intensity of happiness expressions. In contrast, higher anxious attachment was associated with lower average intensity of anger and fear expressions. The results of the study suggest that facial expressions in response to work-related emotion stimuli serve as behavioral indicators of emotion regulation at work and, in particular, attachment-related emotion regulation.